Quality Standards and Labor Market Requirements in Curricula of Faculty of Education at Misurata University - Bennassr, Mustafa; Eqzeet, Huda ((Faculty of Arts Journal) مجلة كلية الآداب - جامعة مصراتة, 2021)
The research aims to identify the availability of quality standards and labor market requirements in the curricula of Faculty of Education, Misurata University from the point of view of the teaching stuff, and whether there is a difference in the opinions of faculty teaching stuff about the availability of quality standards and labor market requirements in the curricula of the Faculty of Education at University Misurata according to the two variables (educational qualification, years of experience), and the research community represents all (217) teaching stuff in the Faculty of Education, Misurata University. The researchers relied on the questionnaire as a tool for data collection consisting of six fields (educational objectives - communication with the community - curriculum content design - educational activities - evaluation – training). Based on the answers to the research questions, these results have been concluded The quality standards and labor market requirements in the curricula of the Faculty of Education, Misurata University were available at an average level from the point of view of the teaching stuff. There are no differences between the averages of the sample’s opinions about quality standards and labor market requirements in the curriculum of the faculty of Education, Misurata University due to the variable (educational qualification). There are no differences between the average opinions of the sample about quality standards and labor market requirements in the curriculum of the faculty of Education, University of Misurata due to the variable (years of experience).